A Dissolution‐Regeneration Route to Synthesize Blue Tungsten Oxide Flowers and their Applications in Photocatalysis and Gas Sensing. Issue 1 (12th October 2015) - Song, Xiang‐Ning; Wang, Chu‐Ya; Wang, Wei‐Kang; Zhang, Xing; Hou, Nan‐Nan; Yu, Han‐Qing
Abstract : Tungsten oxide (WO3 ) has unique physicochemical properties. Although various synthetic methods have been proposed to fabricate tungsten oxide with different morphologies, methods of tailoring the tungsten oxide nanostructure toward new morphologies are still needed. In this work, a self‐assembled WO3 ·0.33H2 O nanoflower is synthesized using a dissolution and regeneration method. In such a two‐step synthetic process, temperature, solvent, and reaction times are found to be the main parameters affecting the morphology of WO3 ·0.33H2 O. The synthesized WO3 ·0.33H2 O nanoflower exhibits a localized surface plasmon resonance effect and a high photocatalytic activity, which can be explained by the doping of W 5+ and its morphology. Furthermore, this WO3 ·0.33H2 O nanoflower can also be used as a gas sensor and has good selectivity and linearity towards acetone vapor in the range of 50–500 ppm. Abstract : Blue WO3 ·0.33H2 O is synthesized through a dissolution‐regeneration route, which is self‐assembled by nanoplates. The blue WO3 ·0.33H2 O exhibits good photocatalytic removal of RhB and gas sensing of acetone.